The diary of a young girl : the definitive edition - Frank, Anne, 1929-1945.; Frank, Otto, 1889-1980.; Pressler, Mirjam; Massotty, Susan (New York : Bantam, 1997)
Compelling and candid, this diary introduced the world to a girl filled with the emotional concerns of a typical teenager, but living in stifling and terrifying circumstances.
Keywords: Frank, Anne, -- 1929-1945 -- Diaries; Netherlands -- History -- German occupation, 1940-1945.; Holocaust, Jewish (1939-1945) -- Netherlands -- Amsterdam -- Personal narratives; Jews -- Persecutions -- Netherlands -- Amsterdam; Jews -- Netherlands -- Amsterdam -- Diaries; Amsterdam (Netherlands) -- Ethnic relations; Frank, Anne, -- 1929-1945 -- Journal intime